(untitled) (Medical Forum Monthly, 2024)
Objective: The objective was to calculate the sensitivity and specificity of C reactive protein and Total leukocyte count by taking histopathological diagnosis of acute appendicitis as the gold standard. Study Design: Observational study Place and Duration of Study: This study was conducted in the Surgical Unit of Lady Reading Hospital, Peshawar from January 2014 to December 2014. Materials and Methods: The study included 50 adult patients of either gender with clinical diagnosis of acute appendicitis. The patients were admitted through the emergency department. The decision to operate was made by the senior surgeon on call, on the basis of clinical features. All the cases were operated within 12 hours’ of admission. Blood samples for Total leukocyte count and C-reactive protein measurement were collected from all the patients before surgery. Operative findings were recorded. Removed appendices were sent for histology. The data was entered and processed on the SPSS 16 version. Results: The patients included 32 males and 18 females. Male to female ratio was 1.8:1. Mean age was 24 years. Frequency of negative appendicectomy was 16%. Sensitivity, specificity and positive predictive value of Total leukocyte count were 80.5%, 62.5% and 91.8% respectively. Sensitivity, specificity and positive predictive value of C-reactive protein were 85.7%, 75% and 94.5% respectively. In patients with histopathologically confirmed acute appendicitis, both the TLC and C - reactive protein were found to be statistically significant. Conclusion: C-reactive protein and Total Leukocyte Count supplement the clinical diagnosis of acute appendicitis.